Axion in a 3-3-1 Model with Right-handed Neutrinos - Soa, Dang Van; Tham, Tran Dinh (Communications in Physics, 2013)
We  show that Peccei - Quinn(PQ) symmetry can be a natural outcomein the 3-3-1 model with right neutrinos after imposing a\(Z_{11}\bigotimes Z_{2}\) symmetry. This symmetry is suitableaccommodated in this model when we augmented its spectrum byincluding a singlet scalar field with large VEV. After breakingthe PQ symmetry yielding the axion we study the decay of axioninto two photons. The result shows that the lifetime of axion isvery long, therefore the axion can play the role of the latedecaying particle(LDP) in a dark matter and it is stable in ouruniverse